Therapeutic effect of Chinese herbal medicines for post-stroke depression: A meta-analysis of randomized controlled trials. Issue 1 (8th January 2021) - Zhang, Huajun; Li, Ming; Xu, Tianshu
Abstract: Background: Whether the addition of Chinese herbal medicine (CHM) in routine western medicines for post-stroke depression yields additional therapeutic effects still remains to be controversial. This study aimed to assess the efficacy and safety of combination of CHM with routine western medicines versus routine western medicines alone in patients with post-stroke depression (PSD). Methods: Electronic databases such as PubMed, EmBase, Cochrane library, and China National Knowledge Infrastructure were systematically searched from inception till October 2019. Studies designed as randomized controlled trials (RCTs) and that investigated the therapeutic effects of CHM plus routine western medicines (CHM group) versus routine western medicines alone (control group) in PSD patients were eligible. The relative risk (RR) and weighted mean difference (WMD) with 95% confidence interval (CI) were used to assess the categories and continuous data using random-effects model. Software STATA was applied to perform statistical analysis (Version 10.0; StataCorp, TX, ). Results: A total of 18 RCTs involving a total of 1, 367 PSD patients were selected for final analysis. The effective rate in CHM group was significantly higher than that in control group (RR: 1.18; 95%CI: 1.12–1.24; P < .001). Moreover, patients in CHM group showed association with lower Hamilton Depression Rating Scale (WMD: -3.17; 95%CI: -4.12 to -2.22; P < .001) and Scandinavian Stroke Scale (WMD: -3.84; 95%CI: -5.73 to -1.96; P < .001) than those in control group. Furthermore, patients in CHM were associated with high level of Barthel Index than those in control group (WMD: 11.06; 95%CI: 4.01 to 18.10; P = .002). Finally, patients in CHM group had lower risk of gastrointestinal (RR: 0.49; 95%CI: 0.31–0.77; P = .002) and neurological (RR: 0.50; 95%CI: 0.33–0.75; P = .001) adverse events than those in control group. Conclusions: The study findings revealed that addition of CHM to routine therapies could improve the therapeutic effects and reduce gastrointestinal or neurological adverse events. Abstract : Supplemental Digital Content is available in the text